2020
DOI: 10.3389/fpsyt.2020.00531
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Trauma, Personality, and Substance Use Disorder: The Development of a Neuropsychoanalytic Addiction Model

Abstract: Background: While traditional psychoanalysis has been criticized as insufficient for the treatment of substance use disorder (SUD), recent progress in the field of neuropsychoanalysis has generated new and promising hypotheses regarding its etiology. However, empirical research applying this framework has been sparse. Aim and Scope: The present overview aims at developing and empirically validating a neuroscientifically informed psychodynamic framework regarding the etiology of SUD. For this purpose, this revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 148 publications
(253 reference statements)
0
7
0
Order By: Relevance
“…In this regard, drug use is an extreme strategy usually linked to extreme adversities, such as sexual abuse, which is also more prevalent in women (Pereda et al, 2014; Villanueva & Gomis‐Pomares, 2021), and at the same time, closely linked to internalising problems (Muniz et al, 2019). According to previous studies (Fuchshuber & Unterrainer, 2020), feelings of anxiety and pain associated with early childhood trauma are often managed by the child ignoring his or her own feelings and self‐esteem. In adulthood, this internalised coping strategy may predispose them to risky behaviours such as drug use.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, drug use is an extreme strategy usually linked to extreme adversities, such as sexual abuse, which is also more prevalent in women (Pereda et al, 2014; Villanueva & Gomis‐Pomares, 2021), and at the same time, closely linked to internalising problems (Muniz et al, 2019). According to previous studies (Fuchshuber & Unterrainer, 2020), feelings of anxiety and pain associated with early childhood trauma are often managed by the child ignoring his or her own feelings and self‐esteem. In adulthood, this internalised coping strategy may predispose them to risky behaviours such as drug use.…”
Section: Discussionmentioning
confidence: 99%
“…Based on his studies on mammalian brains, Jaak Panksepp identified areas in the subcortical-limbic circuits of the brain to be the seat of seven primal emotion systems (Panksepp, 2004;Fuchshuber et al, 2019Fuchshuber et al, , 2022, which he derived from electrical stimulation of specific neuronal networks, namely SEEKING/foraging, PLAY/joy, CARE/nurturance, LUST/sexuality; PANIC/separation, RAGE/anger, and FEAR/anxiety. Within contemporary psychoanalytic discourse these affective systems are currently discussed regarding reconceptualization of classical drive theory (Fuchshuber and Unterrainer, 2020;Solms, 2021;Kernberg, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, Fuchshuber et al ( 12 ) developed The German Version of the Brief Affective Neuroscience Personality Scales including a LUST scale (BANPS–GL). Regarding the impact of primary emotions on the pathogenesis of SUDs recent studies emphasize dysregulations especially within the SEEKING, the SADNESS and the ANGER systems ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%